Effect Of Volume Fraction For Different Thermophysical Properties Of Carbon Nanotube Nanofluid - Yaacob, Nuradlin Athirah (Universiti Sains Malaysia, 2021)
Nanofluids comprise of base fluid and naoparticles. Nanoparticle comprises of 4 elements which are metallic, oxide, carbon and also nano-droplet. There are various types of carbon nanoparticle such as Carbon Nanotubes (CNTs) and Graphene. Nowadays, the most common types used in most industries is Carbon Nanotubes due to its great thermophysical properties which able to help in certain applications such as heat transfer application, biomedical application (nanodrug delivery & cancer therapeutics) and cooling of microchips. There are two ways in order to determine the thermophysical properties of nanofluid which are by experimental and simulation work. However, the experimental work is expensive, time – consuming and requires great effort and sufficient knowledge on the experimental procedure. Therefore, in this present study, Molecular Dynamic (MD) Simulation with computation of Green Kubo formularization had been carried out to simulate the thermophysical properties of CNT nanofluids, specifically thermal conductivity, dynamic viscosity, total energy and density at volume fraction 2.7%, 2.9% and 5.3% of CNT nanoparticles. The result of simulated total energy of CNT nanofluid was utilized to calculate specific heat of CNT nanofluid at all volume fraction stated above. The main aim is to determine the effect of volume fraction on the thermophysical properties of CNT nanofluids. The dynamic viscosity results of CNT nanofluid shows 0.5% to 0.6% increment when the volume fraction increases. The density results of CNT nanofluid shows 0.1% to 0.4% increment when the volume fraction increases. The specific heat results of CNT nanofluids shows 5% reduction when the volume fraction increases. These results are consistent with recent published work. Next, the thermal conductivity of CNT nanofluid shows reduction when volume fraction increases which is inaccurate. Hence, the thermal conductivity of CNT nanofluid was also calculated by using theoretical formulae of Maxwell Equation and the results shows 1% to 6% increment when the volume fraction increases. This result is consistent with recent published work.